Optimalisasi Penanggulangan Bencana Alam Melalui Program Pengabdian Masyarakat (Studi Lokasi: Desa Taba Pasmah Kec. Talang Empat Kab. Bengkulu Tengah) - Taufik Hidayat; Hesvi Tri Yulia; Putri Sundari; Muhammad Reza Syah; Maulana, Husin; Kharisma Yogi Marselina; Sulastri Safitri; Salsabila Izati; Cylen Febiara; Veni Listiana Ekasari (MENYALA: Jurnal Pengabdian Masyarakat, 2024)
Indonesia is a country that often experiences the rainy season. Humid temperatures cause very high temperatures. Around Indonesia, it experiences heavy rain when it occurs. This situation has an influence on the condition of Indonesia in terms of both good and bad. Taba Pasmah Village is an area located in various lowlands. If the rainy season occurs there are many disasters because the river flow is very high.  The aim of the research is to provide awareness to the public about the importance of disaster signs, including evacuation routes. Activities are carried out in various stages of going directly into the field, preparation and implementation stages. This method is used as a way to provide understanding, question and answer and practice. The results obtained by having evacuation routes can anticipate the impacts that occur on communities in areas prone to natural disasters. In this case, it can be used as an activity so that it can be useful for the wider community, especially in Taba Pasmah village.